Hypokalemic Periodic Paralysis: Reports of Two Cases and Brief Review (BIRDEM Medical Journal, 2019)
Hypokalemic periodic paralysis (HPP) is a rare autosomal dominant channelopathy characterized by skeletal muscle weakness or paralysis when there is a fall in potassium levels in blood. Weakness may be mild and limited to certain muscle groups or more severe causing generalized paralysis. During an attack, reflexes may be diminished or absent. Attacks may last for a few hours or persist for several days, ultimately resulting in complete recovery. Some patients may develop chronic muscle weakness later in life. Recurrent muscle weakness accompanied by hypokalemia and exclusion of other causes help establish the diagnosis. Potassium supplementation is the mainstay of treatment of acute illness. Lifestyle modification with or without pharmacotherapy in the form of carbonic anhydrase inhibitors and/ or spironolactone can prevent future attacks. Here, we present two cases of HPP, the first one had no positive family history and responded to oral potassium and spironolactone, while the second case had family history suggestive of HPP and was managed with potassium and eplerenone.Birdem Med J 2019; 9(1): 74-79